2018
DOI: 10.1002/mds.27576
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor subthalamic stimulation restores risk‐reward trade‐off in Parkinson's disease

Abstract: A BS TRACT: Background: STN-DBS effectively treats motor symptoms of advanced PD. Nonmotor cognitive symptoms, such as impaired impulse control or decision making, may either improve or worsen with DBS. A potential mediating factor of DBS-induced modulation of cognition is the electrode position within the STN with regard to functional subareas of parallel motor, cognitive, and affective basal ganglia loops. However, to date, the volume of tissue activated and weighted stimulation of STN motor versus nonmotor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 82 publications
2
31
0
Order By: Relevance
“…Impulsivity scores on the Barratt Impulsiveness Scale (BIS-11, Patton and Stanford, 1995) were measured in six studies (total of 165 patients) comparing scores either between DBS On and Off conditions (Torta et al, 2012;Seinstra et al, 2016), or between DBS On and PD-patients On medication or healthy controls (Hälbig et al, 2009;Evens et al, 2015;Hagelweide et al, 2018;Irmen et al, 2019). One study reported significantly worse impulsivity scores in a DBS-group compared to healthy controls (Hälbig et al, 2009).…”
Section: Clinical Scalesmentioning
confidence: 99%
“…Impulsivity scores on the Barratt Impulsiveness Scale (BIS-11, Patton and Stanford, 1995) were measured in six studies (total of 165 patients) comparing scores either between DBS On and Off conditions (Torta et al, 2012;Seinstra et al, 2016), or between DBS On and PD-patients On medication or healthy controls (Hälbig et al, 2009;Evens et al, 2015;Hagelweide et al, 2018;Irmen et al, 2019). One study reported significantly worse impulsivity scores in a DBS-group compared to healthy controls (Hälbig et al, 2009).…”
Section: Clinical Scalesmentioning
confidence: 99%
“…Although STN-sensorimotor-cortex connectivity has primarily been associated with improvements in motor performances a recent study showed mood improvement actually relies on DBS of the motor STN 47 . Similarly, motor STN stimulation can normalize cognitive performance 48 . This implicates the overlapping presence of affective/associative and motor processing neurons in the STN motor segment 4 and suggests that retuning the motor loop may improve non-motor features as well.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have validated the pipeline using electrophysiological recordings 52,53 and others have demonstrated that results are capable of explaining clinical improvements across patients, DBS centers and cohorts 2,3,48,54,55 . Still, residual errors of electrode reconstructions cannot be excluded.…”
Section: Stn-dbsmentioning
confidence: 99%
“…De Almeida showed that functional connectivity between STN-DBS electrodes and a specific site in the ipsilateral cerebellum was associated with partly restoring motor learning in PD patients (de Almeida Marcelino et al, 2019). Finally, focusing on localized instead of connectivity-mediated effects, Irmen et al showed that modulating specific subregions of the STN could restore risk-taking behavior to a level observed in healthy controls (Irmen et al, 2019a).…”
Section: A Tool To Shift Dbs Imaging Research To a Group Levelmentioning
confidence: 99%
“…The application is continuously extended to other indications and targets (for a review see Lozano and Lipsman, 2013). Aside from its clinical value, DBS opens an invaluable window to the human brain and it is increasingly adopted to probe causal relationships between stimulated targets and certain behavioral effects, such as risk control (Irmen et al, 2019a;Nachev et al, 2015), movement speed (W.-J. , memory learning (de Almeida Marcelino et al, 2019) or verbal fluency (Ehlen et al, 2017;Mikos et al, 2011).…”
Section: Introductionmentioning
confidence: 99%